Distal Radial Artery Access for Superficial Femoral Artery Interventions. (April 2021) - Ruzsa, Zoltán; Csavajda, Ádám; Nemes, Balázs; Deák, Mónika; Sótonyi, Péter; Bertrand, Olivier F.; Merkely, Béla
Purpose: To compare the acute success and complication rates of distal radial (DR) vs proximal radial (PR) artery access for superficial femoral artery (SFA) interventions. Materials and Methods: Between 2016 and 2019, 195 consecutive patients with symptomatic SFA stenosis were treated via DR (n=38) or PR (n=157) access using a sheathless guide. Secondary access was achieved through the pedal artery when necessary. The main outcomes were technical success, major adverse events (MAEs), and access site complications. Secondary outcomes were treatment success, fluoroscopy time, radiation dose, procedure time, and crossover rate to another puncture site. Results: Overall technical success was achieved in 188 patients (96.4%): 37 of 38 patients (97.3%) in the DR group and 151 of 157 patients (96.2%) in the PR group (p=0.9). Dual (transradial and transpedal) access was used in 14 patients (36.8%) in the DR group and 28 patients (18.9%) in the PR group (p<0.01). Chronic total occlusions were recanalized in 25 of 26 DR patients (96.1%) and in 79 of 81 PR patients (92.6%) (p=0.57). The crossover rate to femoral access was 0% in the DR group vs 3.2% in the PR group (p=0.59). Stents were implanted in the SFA in 15 DR patients (39.4%) and in 39 patients (24.8%) in the PR group (p=0.1). The contrast volume, fluoroscopy time, radiation dose, and procedure time were not statistically different between the DR and PR groups, nor were the rates of access site complications (2.6% and 7.0%, respectively). The cumulative incidences of MAE at 6 months in the DR and PR groups were 15.7% vs 14.6%, respectively (p=0.8). Conclusion: SFA interventions can be safely and effectively performed using PR or DR access with acceptable morbidity and a high technical success rate. DR access is associated with few access site complications.